2016
DOI: 10.1093/schbul/sbw093
|View full text |Cite
|
Sign up to set email alerts
|

Modality-Dependent Impact of Hallucinations on Low-Frequency Fluctuations in Schizophrenia

Abstract: Prior resting-state functional magnetic resonance imaging (fMRI) analyses have identified patterns of functional connectivity associated with hallucinations in schizophrenia (Sz). In this study, we performed an analysis of the mean amplitude of low-frequency fluctuations (ALFF) to compare resting state spontaneous low-frequency fluctuations in patients with Sz who report experiencing hallucinations impacting different sensory modalities. By exploring dynamics across 2 low-frequency passbands (slow-4 and slow-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 31 publications
3
34
0
Order By: Relevance
“…In addition, Fryer et al used voxel wise amplitude of low-frequency fluctuations (ALFF) between frequencies 0.01-0.08 to find that SZs have lower ALFF compared to TCs especially in posterior cortex, occipital and cerebellar lobes (Fryer, et al, 2016). This observation has been reported in other studies as well (Alonso-Solis, et al, 2017;Calhoun, et al, 2012;Hare, et al, 2017;Hoptman, et al, 2010). On the other hand, Alonso-Solis et al report that ALFF for SZ is higher than that of TCs in insula (Alonso-Solis, et al, 2017).…”
Section: Schizophrenia-related Findingsmentioning
confidence: 87%
“…In addition, Fryer et al used voxel wise amplitude of low-frequency fluctuations (ALFF) between frequencies 0.01-0.08 to find that SZs have lower ALFF compared to TCs especially in posterior cortex, occipital and cerebellar lobes (Fryer, et al, 2016). This observation has been reported in other studies as well (Alonso-Solis, et al, 2017;Calhoun, et al, 2012;Hare, et al, 2017;Hoptman, et al, 2010). On the other hand, Alonso-Solis et al report that ALFF for SZ is higher than that of TCs in insula (Alonso-Solis, et al, 2017).…”
Section: Schizophrenia-related Findingsmentioning
confidence: 87%
“…One important strength of this study was assessing variability separately at slow4 and slow5. Frequency-dependent variability alterations in region-specific brain areas have been reported at slow4 and slow5 in different disorders [41][42][43][44][45][46] . These results suggest both disease-and frequency-dependent disruptions of variability patterns.…”
Section: Discussionmentioning
confidence: 99%
“…ALFF, which quantifies local resting‐state signal fluctuations, was calculated as the integral of signal amplitude in the low‐frequency domain (0.009–0.08 Hz) [Zou et al, ]. The subject‐level voxelwise ALFF map was converted into a z‐score map by subtracting the mean ALFF of the whole brain and dividing by the standard deviation [Hare et al, ; Zang et al, ; Zou et al, 2010, ]. We decomposed the ALFF calculation in the low‐frequency range into two bands as previously described [Buzsaki and Draguhn, ; Han et al, ; Hare et al, ; Zuo et al, ], i.e., slow‐4 (ALFFs4, 0.027–0.073 Hz) and slow‐5 (ALFFs5, 0.01–0.027 Hz).…”
Section: Methodsmentioning
confidence: 99%
“…Resting‐state fMRI has emerged as a powerful tool for mapping the spontaneous functional activity of the human brain noninvasively, and it is particularly useful for clinical populations, such as ABI patients [Di Perri et al, ; Sharp et al, ]. The amplitude of low‐frequency fluctuation (ALFF, generally in the range of 0.01–0.08 Hz) [Zang et al, ] is an efficient index that quantifies resting‐state local spontaneous neuronal activity, reflects the regional metabolic level of glucose [Aiello et al, ], shows high test–retest reliability particularly suitable for longitudinal observations [Zuo et al, ], and has been widely adopted in clinical studies [Han et al, ; Hare et al, ; Lui et al, ; Meda et al, ] which closely correlates with clinical symptoms [Hare et al, ; Lui et al, ]. By decomposing the low‐frequency fluctuations into slow‐4 (0.027–0.073 Hz) and slow‐5 (0.01–0.027 Hz) frequency bands consistent with Buzkasi's theory [Buzsaki and Draguhn, ], Meda and colleagues reported that ALFF in slow‐4 and slow‐5 might play complementary roles underlying the physiologic mechanisms for psychosis [Meda et al, ].…”
Section: Introductionmentioning
confidence: 99%